Deep brain stimulation in the globus pallidus alleviates motor activity defects and abnormal electrical activities of the parafascicular nucleus in parkinsonian rats - Xie, Jinlu; Chen, Zheng; He, Tingting; Zhu, Hengya; Chen, Tingyu; Liu, Chongbin; Fu, Xuyan; Shen, Hong; Li, Tao (Frontiers in Aging Neuroscience, 2022)
Deep brain stimulation (DBS) is an effective treatment for Parkinson's disease (PD). The most common sites targeted for DBS in PD are the globus pallidus internal (GPi) and subthalamic nucleus (STN). However, STN-DBS and GPi-DBS have limited improvement in some symptoms and even aggravate disease symptoms. Therefore, discovering new targets is more helpful for treating refractory symptoms of PD. Therefore, our study selected a new brain region, the lateral globus pallidus (GP), as the target of DBS, and the study found that GP-DBS can improve motor symptoms. It has been reported that the thalamic parafascicular (PF) nucleus is strongly related to PD pathology. Moreover, the PF nucleus and GP have very close direct and indirect fiber connections. However, whether GP-DBS can change the activity of the PF remains unclear. Therefore, in this study, we monitored the activity changes in the PF nucleus in PD rats during a quiet awake state after GP-DBS. We found that GP-DBS could reverse the electrical activity of the PF nucleus in PD model rats, including the discharge pattern of the neurons and the local field potential (0.7–12 and 12–70 Hz). Based on the results mentioned above, PF activity in PD model rats could be changed by GP-DBS. Thus, the normalization of PF neuronal activity may be a potential mechanism for GP-DBS in the treatment of PD; these findings lay the foundation for PD treatment strategies.